Reliable software technologies – Ada-Europe 2016 : 21st Ada-Europe International Conference on Reliable Software Technologies, Pisa, Italy, June 13-17, 2016, Proceedings /: 21st Ada-Europe International Conference on Reliable Software Technologies, Pisa, Italy, June 13-17, 2016, Proceedings. (2016) - Unknown
No abstract available